Comparability and reproducibility of apex cardiogram recorded with six different transducer systems. Issue 6 (June 1979) - Willems, J L; Denef, B; Kesteloot, H; De Geest, H
Abstract : A comparison was made in 7 dogs of the results obtained by 6 different apex cardiographic transducers applied before, during, and after controlled infusion of angiotensin and isoprenaline. The electrocardiogram, internal phonocardiogram, aortic and left ventricular pressure using a Telco micromanometer, and apex cardiogram were recorded simultaneously on magnetic tape and paper. Digital computer techniques were used to derive various measurements. The comparison of the 6 transducer systems was made expecially with respect to measurements derived from the normalised derivative, calculated using total as well as developed pressure or displacement. Measurements derived from left ventricular pressure were very reproducible. Differences in results of 'contractility' indices varied between 0.5 and 1.9 per cent. Indices from the apex cardiogram using 6 different transducer systems showed variations up to 20 per cent, with mean values varying between 3.2 and 8.1 per cent. There was a systematic deviation for one transducer system, which was responsible for a significant part of the observed variability. It may be concluded that in order to assure maximal reproducibility, technical characteristics of the apex cardiograph transducer should be taken into account and an optimal recording technique should be used.